2000
DOI: 10.1097/00002030-200001280-00007
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of serum HIV-1 RNA levels in 330 patients with a known date of infection

Abstract: Our study extends to the early post-seroconversion phase the prognostic value of extracellular HIV-1 RNA levels. Moreover, our data suggest that, in most HIV-infected individuals, a progressive loss of control of viral replication arises during the early years of HIV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 42 publications
6
104
1
3
Order By: Relevance
“…In adults, during the period of primary infection, HIV-1 RNA copy number initially rises to high peak levels, rapidly followed by a 2-to 3-log 10 decrease until reaching a steady-state plateau (the virologic "setpoint") within approximately 6 to 9 months after the acquisition of HIV infection. 15,39 In contrast, the initial burst of viremia in children can reach higher values (Ͼ10 6 copies/mL). In addition, RNA copy number slowly declines even without treatment during the first years after birth and persists at higher levels than those observed in most infected adults.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In adults, during the period of primary infection, HIV-1 RNA copy number initially rises to high peak levels, rapidly followed by a 2-to 3-log 10 decrease until reaching a steady-state plateau (the virologic "setpoint") within approximately 6 to 9 months after the acquisition of HIV infection. 15,39 In contrast, the initial burst of viremia in children can reach higher values (Ͼ10 6 copies/mL). In addition, RNA copy number slowly declines even without treatment during the first years after birth and persists at higher levels than those observed in most infected adults.…”
Section: Discussionmentioning
confidence: 98%
“…10 -12 Numerous studies performed in adults have demonstrated that HIV-1 RNA levels are independent predictors of disease progression and have resulted in clinical guidelines. [13][14][15] In contrast, pediatric studies are scarce and antiretroviral therapy (ART) guidelines remain broad. In the Women and Infants Transmission Study cohort, Shearer et al 12 reported that the median HIV-1 RNA levels over the first 2 months of life in infected children were predictive of an increased rate of disease progression.…”
mentioning
confidence: 99%
“…Acute HIV-infected patients (ACUTE, n517) were defined as negative in the presence of HIV antibody but positive for HIV RNA. 22 The average infection time of acute HIV-infected patients was 59 (59635.38) days. Patients with progressive disease with less than 350 CD4 1 cells/ml and requiring highly active antiretroviral therapy (HAART) according to the WHO recommendation within 2 years after diagnosis were classified as fast progressors (FPs, n521), and those who did not require HAART (greater than 350 CD4 1 cells/ml) within 2 years were defined as slow progressors (SPs, n537).…”
Section: Study Subjectsmentioning
confidence: 99%
“…La charge virale plasmatique et le taux de CD4 sont des marqueurs très prédictifs de la progression spontanée ultérieure de la maladie [15,16], qu'ils soient mesurés chez des séroconver-teurs ou chez des sujets diagnostiqués au stade chronique. Des taux de CD4 différents entre les sexes ont été décrits chez des sujets non infectés, soit en population générale [17], soit chez des enfants non infectés nés de mères séropositives [18].…”
Section: Comparaison Des Niveaux Des Marqueurs Cd4 Et Charge Viraleunclassified